Upper Lip Reconstruction after Lip Cancer Wide Excision - Santoso, Boedy Setya; Novastuti, Citra Dwi (Folia Medica Indonesiana, 2019)
Head and neck reconstruction serves two purposes, namely to restore function and aesthetics. The priority goals for lip reconstruction should be determined before surgery. In cases of large lip defects, maintaining the goal makes lip reconstruction difficult. This is a case report of a 66 year old man who came to ORL-HNS OPD, Dr. Soetomo Hospital, Surabaya with the main complaint of ulcers on the upper lip since one year ago accompanied by pain. A mass biopsy result on the right vestibule in Malang on October 11, 2016 showed adenosquamous cell carcinoma. The patient planned to have a wide excision and reconstruction of the lip defect. Wide excision and lip reconstruction was performed on 15 September 2016. Total resection of the upper lip was performed up to the vestibule of the nose. The results showed that squamous cell carcinoma was poorly differentiated. The evaluation after myocutaneous flap surgery was well combined, there were no signs of inflammation or infection. Patients can open their mouths, eat, drink and speak without complaint. The patient then received regular chemoradiotherapy two weeks after surgery.